Multiple Traumas, Maternal Depression, Mother–Child Relationship, Social Support, and Young Children's Behavioral Problems. Issue 1 (January 2021) - Schiff, Miriam; Pat-Horenczyk, Ruth; Ziv, Yuval; Brom, Danny
This study examined whether maternal depression, mother–child relationships, and maternal perceived social support mediate the associations between child's exposure to multiple traumatic events and behavioral problems. We recruited a representative sample of 904 Israeli (Jewish and Arab) mothers and their 2- to 6-year-old children. Data collection was conducted through structured face-to-face interviews with the mothers between July and November 2011. All measures were completed by the mothers. We used the child's and mother's exposure to political violence questionnaires, Child Behavior Checklist (CBCL), a short version of the Parental Acceptance–Rejection Questionnaire (PARQ), the Center for Epidemiologic Studies Depression Scale (CES-D), and the Medical Outcomes Study (MOS) Social Support Survey. The research study model was tested using path analysis. The model showed a very good fit to the data, suggesting that maternal rejection, maternal depression, and social support play an important role in child's behavioral problems in the context of multiple traumatic events. Higher levels of maternal rejection were significantly associated with greater children behavior problems. Maternal rejection mediated the associations between maternal depressive symptoms and child's behavioral problems. Maternal perceived social support mediated the associations between child's exposure to multiple traumatic events and child's behavioral problems; child's exposure to multiple traumatic events was associated with lower levels of maternal perceived social support. In turn, lower levels of perceived social support were associated with higher levels of behavioral problems. In conclusion, in accordance with the "social stress framework, " social support has a mediation role in the association between exposure to traumatic events and child's behavioral problems. Thus, enhancing social support to mothers to young children in the context of multiple traumatic events is essential for children resiliency.